(untitled) (International Journal of Engineering Sciences & Management Research, 2026)
Climate change is a major challenge facing our planet today and pattern of global warming will be more pronounced at high altitude zones, especially those in the tropics and subtropics upto 3 to 5 times faster warming than the rest of world. Continuing climate change is predicted to lead to major changes in the precipitation pattern that affecting the river flows, groundwater recharge, natural hazards, and the ecosystem, as well as to people and their livelihoods. Most part of Kinnaur comes under cold desert with high mountainous area, ranging in altitude from 2,320 to 6,816 meters (7,612 to 22,362 ft), covered with snow. Any variation in precipitation would affect the climate of Kinnaur. Change in precipitation pattern in Himalayan has considerable impact on environment and ecosystem. The river and adjoin grassland and forest ecosystems would be severally affected by the change in the precipitation pattern. It also increase the chances of hydro-meteorological disaster flash flood, Avalanche, flood, Glacier lake outburst flood (GLOF), changing vegetation pattern, shifting of snowline etc. For know the impact of climate change on precipitation pattern, we studied 100 year precipitation (year 1914 – 2013) data of Kinnaur and concluded that there is series of wet and dry period for 25 year & studied of average precipitation for 50 years indicated that average precipitation has been increases since year 1964. Above data also indicated that next 20-25 years will be wet period for Kinnaur and chances of hydro-meteorological disaster will be increased.